Effects of policy and functional (in)coherence on coordination – A comparative analysis of cross-sectoral water management problems. Issue 131 (May 2022) - Dombrowsky, Ines; Lenschow, Andrea; Meergans, Franziska; Schütze, Nora; Lukat, Evelyn; Stein, Ulf; Yousefi, Ali
Abstract: Coherence and coordination among interdependent policy sectors are considered key for the implementation of the 2030 Agenda for Sustainable Development. Literature on policy coherence argues that a lack of coordination may lead to policy incoherence; however, literature on coordination also sometimes points to the reversed causality that incoherencies in policies or in governance functions (functional incoherence) may hinder coordinated policy outcomes; in fact, these assumptions have rarely been further theorized or tested empirically. In this paper, we hypothesize the higher functional or policy coherence, the higher coordination at process level and the higher the likelihood that coordination at process level is translated into coordination at outcome level. We test this hypothesis for cross-sectoral coordination challenges among different water using sectors in six different basins located in Germany, Iran, Mongolia, Spain, and South Africa. At first glance, four cases seem to confirm the first part of the hypothesis for functional coherence and three for policy coherence. It remains difficult to establish causality. Whether functional and policy coherence translate into coordination at process level seems to depend on a functioning coordination body. We further find that functional and policy incoherencies may either lead to coordination problems (in view of conflicts of interest) or even go along with a high level of coordination at the process level, possibly to compensate for incoherencies. Neither functional nor policy coherence change the relationship of coordination at process and outcome level. To explain coordination at the outcome level, other factors need to be considered. Highlights: The paper explores how (in)coherence in policies and responsibilities affects coordination at process and outcome level. It presents a rigorous comparative study of cross-sectoral coordination in six river basins worldwide. Coherence may be conducive towards coordination at process level, but it remains difficult to establish causality. Incoherencies may both hinder or stimulate coordination at process level. Coherence in policies and responsibilities does not change the relationship of coordination at process and outcome level.